ANALISIS PENGARUH PERSEPSI HARGA, PERSEPSI KUALITAS PRODUK, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR SUZUKI (Studi Pada Pembeli – Pengguna Sepeda Motor Suzuki di Kota Solo) - Ferdinan, Comaeni Enril; Nugraheni, Rini (Faculty of Economics and Business Diponegoro University, 2013)
This study aims to determine how big the influence perceptiont of price, perceptiont of quality product, and promotion of the buying decision on Suzuki motorcycle in Solo. And this research also aims to analyze the most dominant factors that influence on buying decisions of Suzuki Motorcyle in Solo.The population used in this study is consumers of Suzuki motorcycle around Solo. The sample in this study are 100 respondents and the technique used is non-probability samplingtechnique with the approach of purposive sampling.From the analysis result, the indicators in this study are valid and reliables. The most dominant factor that influence on purchase decisions are promotion, then the perceptiont ofproduct quality, and the last is perceptiont of price. Then though the F Test can be seen that theindependent variables feasible to test the of the dependent variable success product. The result ofAdjusted R Square is 0,439, it means that independen variable can explain about 43,9% of dependen variable